Multispark Discharge in Water as a Method of Environmental Sustainability Problems Solution. (21st July 2013) - Barkhudarov, E. M.; Kossyi, I. A.; Kozlov, Yu. N.; Temchin, S. M.; Taktakishvili, M. I.; Christofi, Nick
Abstract : Multispark discharge excited in water is described, and its useful physical and chemical properties are discussed in the light of some environmental issues. Discharge of such a type generates hot and dense plasmoids producing intense biologically active UV radiation and chemically active radicals, atoms, and molecules. Simultaneously, discharge creates strong hydrodynamic perturbations and cavitation bubbles. Particular attention is given to factors influencing on water purity with special reference to discharge application for effective sterilization of water and its cleaning of harmful chemicals. The gas discharges of this type show considerable promise as a means for solving some actual plasma-chemical problems. The above-mentioned discharge properties have been demonstrated in a series of laboratory experiments, which proved the efficiency of disinfection of potable and waste water, water cleaning of pesticide (herbicide) contaminations, and conversion (recovery) of natural methane.